A preliminary study of nutrients related to the risk of relative energy deficiency in sport (RED-S) in top-performing female amateur triathletes: Results from a nutritional assessment - Langa, D.; Naczyk, M.; Szymczak, R. K.; Karbowska, J.; Kochan, Z. (Nutrients, 2025)
Background/Objectives: As an endurance multi-sport race, triathlon places significant energy demands on athletes during performance and training. Insufficient energy intake from food can lead to low energy availability (LEA) and Relative Energy Deficiency in Sport (RED-S). We aimed to measure symptoms related to LEA, examine the risk of RED-S, and find how diet relates to the risk of RED-S in highly trained female amateur triathletes.